Tensile Properties and Water Absorption of Spear Grass Fibre Filled High Density Polyethylene/Thermoplastic Soya Spent Powder Composites - Sam , Sung Ting; Zulkepli, Nik Noriman; Ismail, Hanafi; Bakar, Sharifah Shahnaz Syed Abu (Taylor's University, 2014)
The study was focused on the tensile properties, morphology, water absorption and thermogravimetric analysis (TGA) of degradable composites which are produced from high density polyethylene (HDPE)/thermoplastic soya spent (TPSS) powder with the addition of spear grass filler. HDPE/TPSS at the ratio of 90:10 was used as matrix in the composites. In this ratio, the tensile strength of the HDPE was not much deteriorated by TPSS. However, significant effect on degradation was observed based on previous research. The addition of spear grass filler has further reduced the tensile strength of the composites, yet the tensile modulus of the composites was improved. Nevertheless, the tensile strength, elongation at break of the composite was improved with the presence of polyethylene grafted maleic anhydride (PE-g-MA) as a compatibiliser. The water absorption shows the increase of the water uptake with the addition of spear grass filler.